2009
DOI: 10.5539/ijbm.v4n10p54
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Intention among Malaysian Undergraduates

Abstract: Research in entrepreneurship field has magnetized the interest of many researchers as a tool of development for many countries. The study of the factors that leads people to become entrepreneurs has been a question of many researchers. This study explores the relationship between the Big-Five personality factors, contextual factors and entrepreneurial intention. As such, it fits squarely into the literature on the antecedents of entrepreneurship. Previous research has focused on the need for achievement as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
106
2
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(128 citation statements)
references
References 25 publications
12
106
2
8
Order By: Relevance
“…This finding of the close correlation between Interpersonal Relationship and entrepreneurial intention supported and supplemented these previous studies [93][94][95][96], whilst implied the impacts of Interpersonal Relationship with sustainable characteristic deserve to be paid more attention. Except for four of the Big Six personality variables, however, similar to Hmieleski and Corbett [75], we found that Openness was not directly related to entrepreneurial intention, and this finding was contradicted with Brice [21] and Ismail et al [97]. The reason could be that the participants with high levels of Openness were college students who were full of motivation and energy, whilst the characteristic might encourage them to simultaneously be sensitive to many new or interesting things, and have broad interests during this period.…”
Section: Discussioncontrasting
confidence: 57%
“…This finding of the close correlation between Interpersonal Relationship and entrepreneurial intention supported and supplemented these previous studies [93][94][95][96], whilst implied the impacts of Interpersonal Relationship with sustainable characteristic deserve to be paid more attention. Except for four of the Big Six personality variables, however, similar to Hmieleski and Corbett [75], we found that Openness was not directly related to entrepreneurial intention, and this finding was contradicted with Brice [21] and Ismail et al [97]. The reason could be that the participants with high levels of Openness were college students who were full of motivation and energy, whilst the characteristic might encourage them to simultaneously be sensitive to many new or interesting things, and have broad interests during this period.…”
Section: Discussioncontrasting
confidence: 57%
“…He also found that those high in agreeableness related negatively to entrepreneurial intent. A third study conducted in Malaysia reported openness and extraversion as being significantly positively related to entrepreneurial intent and the rest of the Big Five as not being related at all (Ismail et al, 2009). A positive relationship between openness and entrepreneurial intent and no relationship between neuroticism and entrepreneurial intent is the only consensus in these studies.…”
Section: Personality and Entrepreneurial Intentionsmentioning
confidence: 84%
“…Lower income countries are looking towards entrepreneurship to spur economic development. Some countries, like Malaysia, are encouraging entrepreneurship with funding and business advisory services (Ismail et al, 2009), and many are looking towards research to help develop entrepreneurs. One branch of entrepreneurial research involves looking into how macro-socioeconomic factors stimulate entrepreneurial intentions; this includes education, media support, and political environments (Alshammari & Al-Tarawneh, 2016).…”
Section: Entrepreneurial Intent and Its Antecedentsmentioning
confidence: 99%
“…This is consistent with the view of Klein and Bullock (2006) that entrepreneurship education should include the management of existing resources, the acquisition new resources, the identification of existing opportunities and the creation new opportunities Souitaris et al (2007) find that entrepreneurship programs significantly raise students' subjective norms and intentions toward entrepreneurship by inspiring them to choose entrepreneurial careers. According to Ismail et al (2009), entrepreneurial education at tertiary level has also become an essential component of many curriculums in higher learning institutions. Since future entrepreneurs can be found amongst those who are currently undergoing their educational process at the universities, entrepreneurship education has been used as one of the most effective ways to promote the transition of graduates into the world of entrepreneurship.…”
Section: The Meaning Of Entrepreneurship Educationmentioning
confidence: 99%